AKTIVITAS EKSTRAK HIBISCUS ROSA-SINENSIS L. DAN BACCAUREA RACEMOSA TERHADAP PERTUMBUHAN RAMBUT PADA ALOPECIA YANG DIINDUKSI STRESS - Putu Indrayoni; Anak Agung Istri Mas Padmiswari (Universitas Islam Negeri Alauddin Makassar, 2022)
Alopecia is the loss of excess hair that causes baldness, either temporarily or permanently. Physical and emotional stress are the most common causes. This study aims to determine the activity of H. rosa-sinensis L. and B. racemosa extracts on stress-induced hair growth in alopecia. Stress induction in male Wistar albino rats was obtained using the tail suspension test (TST) method. The results of the chemical content test were the total phenol content test (4,223.06 mg/100 g), total flavonoid (10,383.12 mg/100 g) and DPPH free radical reduction of B. racemosa (EB) extracts (1,593.17 mg/L GAEAC) were greater than those of the H. rosa-sinensis L. (EH) extract. The longest hair and highest hair density were obtained in the Minoxidil 2% group. While the most hair follicles were found in the group given the combination of EH and EB = 1: 1. The content of phenolic and flavonoid substances affects the hair growth activity. KEYWORDS: alopecia, stress, hibiscus, baccaurea, DPPH